Alteração de gênero como novo risco social e a construção de instrumentos visando a sua efetivação na relação jurídica previdenciária - Souza, Mariana Dias Barreto de (2024)
The aim of this academic doctoral thesis is to discuss, understand and clearly dissociate the possibilities of transgender people's rights under the Brazilian Social Security system, which is silent on the subject. Faced with this vacuum in the legal system and with the aim of proposing legislative changes or judicial decisions that are not activist, we have chosen to dissociate each concept relating to sex, sexual orientation and gender. All with the aim of clarifying doubts or ignorance about these and acting in the most inclusive way for the LGBTQIAP+ community. Thus, based on the deconstructions of gender and, mainly, the binarist conceptions of Social Security Law, when they choose to grant benefits according to the insured person's biological gender, an approach is taken to the benefits of pensions, maternity pay, disability benefits and death pensions. In particular, the aim is to reach people who change their biological gender because they identify with the opposite gender. Furthermore, this new social risk is proven, with the aim of achieving maximum social justice by exposing the reality of the trans population and the helplessness that exists, based on gender prejudice and discrimination. In addition, we examine the concepts of the Federal Council of Medicine, the Federal Council of Psychology, Provision 73 of the National Council of Justice, and the Principle of Yogakarta and mainly the lives of several trans people who were interviewed and used as a basis for the convictions portrayed are examined, respectfully, in this proposal to implement the right in light of the social reality existing in Brazil